Effective Communication Strategies in the Digital Age: Analysis of Habib Ja'far's Content Different but Together Episode 41 - Amalia, Naima Sangidatul; Ula, Nilna Faizatul (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
The rapid advancement of digital technology has transformed Islamic da'wah from traditional spaces into digital platforms, demanding more adaptive and effective communication strategies. This study aims to analyze the communication strategies employed in digital da'wah through a content analysis of the podcast Habib Jafar – Berbeda tapi Bersama episode 41, entitled The Role of Religion in Mental Health. Using a qualitative descriptive approach with content analysis, this study identifies inclusive language, storytelling, humor, and empathetic engagement as key strategies. Unlike previous studies that mainly explore digital da'wah from the perspective of platform usage, this research highlights the intersection between digital da'wah and mental health discourse, making the findings particularly relevant for young audiences who face contemporary psychological challenges. These result contribute both theoretically to the study of Islamic communication and practically to the development of effective digital da'wah strategies.